Cranial sonography as diagnostic tool for neonatal hypoxic ischemic encephalopathy in premature neonates - Yasin, Abeer; Waheed, Shahid; Bhatti, Shahzad Karim; Yousaf, Khalid Rehman; Saadat, Jabran; Iqbal, Asma (Journal of Fatima Jinnah Medical University, 2019)
Background: Perinatal asphyxia plays a major role in neonatal morbidity and death throughout the world. An estimated 130 million infants are born each year, of which 4 million die within first 28 days of life. Pakistan has the third highest neonatal death rate in the world with incidence of prenatal asphyxia reaching up to 9%. Magnetic resonance imaging (MRI) of the brain is the standard imaging modality in such cases, but a good correlation between cranial sonography and MRI of brain has been reported. The aim of this study was to determine diagnostic accuracy of cranial sonography in detection of neonatal hypoxic ischemic encephalopathy (HIE) in clinically suspected premature neonates. Patients and methods: This cross-sectional survey was conducted in Sir Ganga Ram Hospital, Department of Radiology and Medical Imaging between March-August, 2017. Total 303 premature neonates were included in the study hospitalized in Neonatology unit of the hospital with clinical suspicion of hypoxic ischemic encephalopathy. Transcranial sonography (CUS) was performed in first month of life and findings were recorded. Then 1.5 Tesla MRI machine was used for imaging brain using T1-weighted, T2-weighted and fluid-attenuated inversion recovery (FLAIR) sequences. The sonographic results were then compared with MRI findings. Results: The mean age of mothers was 29.3years. The mean gestational age at birth was 33.9weeks. In this study, there were 157 (51.8%) males and 146 (48.2%) female neonates. The sensitivity, specificity, PPV, NPV and diagnostic accuracy of cranial sonography were 97.8%, 96.0%, 97.2%, 96.8% and 97.0%, respectively taking MRI as gold standard